1969
DOI: 10.1063/1.1670903
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Tungsten Bronze-Type Crystal Structures. II. Barium Sodium Niobate Ba(4 + x)Na(2 − 2x)Nb10O30

Abstract: Ferroelectric Ba(4+x)Na(2 − 2x)Nb10O30, with a Curie temperature of 833°K, has a tungsten bronze-type structure and crystallizes in the orthorhombic system, with subcell lattice constants a = 17.59182 ± 0.00001, b = 17.62560 ± 0.00005, and c = 3.994915 ± 0.000004 Å at 298°K. The space group is Cmm2, and there are two formulas in the subcell. The c axis of the true cell is double that of the subcell. The integrated intensities of 6911 reflections within a reciprocal hemisphere of radius (sinθ)/λ = 1.02 Å−1 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(103 citation statements)
references
References 29 publications
2
99
1
1
Order By: Relevance
“…The fundamental averaged structure of BNN at room temperature was determined at the end of the 1960s by Jamieson et al [16]. [20] for K 0.6 FeF 3 , confirming this modulation as generally distinctive of TTB phases and not only of BNN.…”
Section: Structural Characterizationsupporting
confidence: 50%
“…The fundamental averaged structure of BNN at room temperature was determined at the end of the 1960s by Jamieson et al [16]. [20] for K 0.6 FeF 3 , confirming this modulation as generally distinctive of TTB phases and not only of BNN.…”
Section: Structural Characterizationsupporting
confidence: 50%
“…Jamieson et al (1969) showed that, in BNN, the reduction in the O±Nb±O angle along the c direction (from 180 to 165 ) and the ordering of the tilting of O± Nb±O caused the movement of Ba and O (at z = AE1/2c) from their average positions, which accompanied the doubling of the c axis. suggested that a`concerted rotary' displacement of the oxygen in BNN brought about a multiplicity of the tetragonal subcells.…”
Section: Resultsmentioning
confidence: 99%
“…The tetragonal tungsten bronze oxides (TTBs), general formula A1 2 A2 4 B1 2 B2 8 C 4 O 30 , contain perovskite-like units which are inter-linked by an oxide octahedron to form channels 12 with triangular, quadrilateral and pentagonal cross-sections, Figure 1. This relatively open TTB structure can accommodate a wide array of cations resulting in a rich diversity of compositions with this structure type.…”
Section: Introductionmentioning
confidence: 99%